2020
DOI: 10.3905/jod.2020.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Option Pricing with Mixed Lévy Subordinated Price Process and Implied Probability Weighting Function

Abstract: It is essential to incorporate the impact of investor behavior when modeling the dynamics of asset returns. In this paper, we reconcile behavioral finance and rational finance by incorporating investor behavior within the framework of dynamic asset pricing theory. To include the views of investors, we employ the method of subordination which has been proposed in the literature by including business (intrinsic, market) time. We define a mixed Lévy subordinated model by adding a single subordinated Lévy process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In spite of their clear utility for cryptocurrency modeling, Lévy processes have only been recently explored (Philippas et al, 2019). Shirvani et al (2022) propose using a doubly subordinated normal inverse Gaussian Lévy process for daily Bitcoin return data. We push this idea further and show that deeper subordination using the DVG provides better fits of the small log‐returns, but also captures tail behavior better than the model of Shirvani et al (2022).…”
Section: Application To High Frequency Cryptocurrency Returnsmentioning
confidence: 99%
“…In spite of their clear utility for cryptocurrency modeling, Lévy processes have only been recently explored (Philippas et al, 2019). Shirvani et al (2022) propose using a doubly subordinated normal inverse Gaussian Lévy process for daily Bitcoin return data. We push this idea further and show that deeper subordination using the DVG provides better fits of the small log‐returns, but also captures tail behavior better than the model of Shirvani et al (2022).…”
Section: Application To High Frequency Cryptocurrency Returnsmentioning
confidence: 99%
“…To quantify an option trader's fear and greed disposition, Shirvani et al (2019) introduced a new Lèvy process for asset returns in the form of a mixed geometric Brownian motion and subordinated Lèvy process. The mixed subordinated Lèvy process is designed to incorporate the views of investors into log return asset pricing models.…”
Section: Option Pricing For Mixed Subordinated Variance Gamma Processmentioning
confidence: 99%
“…In the mixed subordinated Lèvy log-price process in Equation ( 46),  ≠ 0 is the volatility of the continuous dynamics of X, and s is the volatility of the pure jump of the subordinated process L V t . Shirvani et al (2019) used the mean-correction martingale measure 36 method to price options. By applying this method, the authors showed that the proposed pricing model is indeed arbitrage free.…”
Section: T S T T S T R T S T T S Tmentioning
confidence: 99%
“…The mentioned issues have been considered in recent research in recent decades. But, other factors such as forecasting or numerical issues based on economic models need to be considered soon [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%